Nursing support time as a people management indicator - Alda Valéria Neves Soares; Karin Emília Rogenski; Fernanda Maria Togeiro Fugulin; Antonio Fernandes Costa Lima; Tânia Regina Sancinetti; Raquel Rapone Gaidzinski (O Mundo da Saúde, 2011)
This experience report aimed at showing the use of the variable on nursing support time as a people management indicator. To obtain and systematically evaluate the data, one created an Excel worksheet and used the equations proposed in the Gaidzinski’s method on personnel size. The support time data according to the care category were compared to the standard established by COFEN (Federal Nursing Council) Resolution N. 293/04, allowing the nursing service manager to monitor the qualitative and quantitative compliance of the existing picture. The information derived from the indicator on average support time subsidizes the proposition of interventions that assure the support quality improvement and the safety of patients and nursing professionals.